Efeito do laser Nd:Yag no pré-tratamento dentinário e selamento marginal, em restaurações de cimento de ionômero de vidro resina modificado - Lima, Dimas Renó de [UNESP] (2003)
The purpose of this study was to evaluate the marginal sealing of resin modified glass ionomer cement restorations after the application of the Nd:YAG laser on the primer, light cured or not, and on the margins of the restoration using the micro leakage test. 120 class V restorations on the vestibular and lingual surfaces of each tooth were performed, divided into six groups in which the effects of the Nd:YAG laser on the denun and on the margins of the restoration were obseved. The specimens were thermocycled at 5°C and 55°C, ± 2°C, and immersed in 50% silver nitrate solution. A cut in the center of the restoration in the vestibular lingual direction to determine the degree of microleakage in the occlusal and gingival margins of each specimen was performed. The statistical methods Kruskal-Wallis, non-parametric, and the Wilcoxon's Paired Signed Rank Test were used at 5% significance level. The methodology used to evaluate the marginal leakage made it possible to conclude that: all groups presented similar micro leakage results for the occlusal and gingival margins and were not statistically different between them; when the degrees of micro leakage were compared between the occlusal and gingival margins it was observed that groups II and Ill did not present significant statistical difference, while groups I, IV, V and VI presented significant statistical differences; when the occlusal margin was compared to the gingival, a smaller gingival marginal leakage was observed